A "borderline case" of syntactic variation. Issue 1 (6th March 2020) - Brandner, Ellen
Abstract : Dialectal maps of morpho-syntactic phenomena sometimes display patterns that either differ quite drastically from the traditional dialectal boundaries (which are mostly based on phonology or the lexicon) or show otherwise unexpected patterns. This paper argues to take these deviations seriously, namely as a potential tool to detect the different types and qualities of syntactic micro-variation. As a case study, differing patterns concerning the distribution of the infinitival marker zu across various infinitival constructions within the Alemannic dialect group will be examined and it will be argued that an analysis of the infinitival marker as the lexical realization of the [±coin] value within a theory of temporal anchoring, as proposed in Ritter & Wiltschko (2014 ), provides the necessary flexibility in order to capture these differing variational patterns.